Comparative Economic Evaluation of Integrated and Non-integrated Farming Systems in Northeastern Karnataka, India - , Nalinashree R N; , Aravinda B J; , Srinatha T N; , Manish K L; , Hemanth D B; , Popavath Bhargav Naik; , Pavan Kumar Kumawat; , Jagadeesh M S (Archives of Current Research International, 2024)
Integrated Farming System (IFS) represented a holistic approach to managing farm resources, aimed at boosting productivity, minimizing environmental impact, enhancing incomes for resource-poor farmers, and ensuring agricultural sustainability. Multi-stage random sampling technique was used, beginning with Ballari district, followed by selecting one taluk with the highest net sown area, and then two villages within that taluk. From each village, 10 IFS and 10 non-IFS farmers were randomly selected, totaling 40 farmers. This study analyzed the costs and returns of major IFS and non-IFS practices in Ballari district, Karnataka. Data were collected from 40 farmers in two villages within Ballari taluk during the agricultural year 2017-18 and were analyzed using tabular and budgeting methods. The results revealed that farmers in the area used three distinct farming systems: IFS-I (Crop + Dairy), IFS-II (Crop + Dairy + Small Ruminants), and Non-IFS (Crop only). Major crops included paddy, dry chili, cotton, and jowar. The analysis showed that IFS-II, which integrated crops, dairy, and small ruminants, generated the highest net returns at ₹1,57,220.04, followed by IFS-I with ₹1,35,625.20, and Non-IFS with ₹60,698.11. To maximize benefits, there was a need to promote IFS-II more widely among farmers. Efforts were suggested through Raitha Samparka Kendra (RSK) and Krishi Vigyana Kendra (KVK) to advocate for IFS adoption, thereby enabling more efficient use of farm resources and improving productivity and profitability for farming households.